A balanced view of impossible aesthetics: An empirical investigation of how impossibility relates to our enjoyment of magic tricks. (January 2023) - Bagienski, Steven E; Kuhn, Gustav
The performance art of magic allows us to experience the impossible, and this study used a balancing magic trick to investigate the relationship between participants' enjoyment and perceived impossibility. Participants watched a live performance of a magic trick in which the magician balanced objects in progressively more impossible configurations. At seven different time points observers rated their enjoyment, and the extent to which they believed what they saw was impossible. Regression analysis revealed that participants' enjoyment of the magical effect relates to their perceived impossibility of the magic trick, and this relationship was independent of how much they enjoyed magic in general. Moreover, a one-way within-subjects analysis of variance showed that participants enjoyed the performance More as the trick became more impossible. However, once the magical effect was anticipated, enjoyment began to plateau while perceived impossibility continued to increase. These results are discussed in the context of people's aesthetic appreciation of magic and current arts appreciation models.